Understanding Teacher Agency During Curriculum Transitions: A Case Study of Secondary School Natural Science Teachers in South Africa - Matlhodi Motsepe; Thomas Sedumedi; Mmushetji Rankhumise (PSEJ (Pancasakti Science Education Journal), 2026)
In South Africa, curriculum change remains a crucial national concern, particularly in secondary schools, where educational reform efforts intersect with broader concerns about equity, access to knowledge, and teacher autonomy. This study investigates how secondary school teachers understand and enact their professional agency in the face of curriculum change. Using an ecological framework of an agency, it examines how teachers perceive their roles as change agents, the factors that affect their choices, and their interaction with policy-driven changes. Using a quantitative design, the study collected responses through a structured questionnaire administered in 41 schools in the Northwest province of South Africa. Descriptive statistical analysis showed that although many teachers demonstrate a strong sense of professional responsibility and a deep commitment to curriculum goals, they are frequently constrained in their ability to act by external factors, including unequal access to resources, top-down policy mandates, and inadequate professional development. According to the results, teacher agency is influenced by the relationships they build within those settings, as well as by the institutional contexts in which they operate. In the end, the study emphasizes the necessity of rethinking teacher development frameworks to prioritize teacher voice, foster local innovation, and promote agency as a major factor in meaningful curriculum reform. For policymakers, school administrators, and curriculum developers seeking a more inclusive and responsive science education system in post-apartheid South Africa, these insights have significant implications.